MULTI DISABLE PEOPLE NEEDS' PROFILE - A COMPREHENSIVE APPROACH - Khawla Yahya Hawamdeh; Cristina Skrypnyk (European Scientific Journal, ESJ, 2013)
Persons with multi disabilities are individuals of all ages who require extensive ongoing support in more than one major life activity to participate in integrated community settings. The study intented to identify the physical, educational, social and emotional needs of the multi disable people in an attempt to gain a better understanding of the factors influencing their life. A questionnaire with 80 items distributed on 4 domains, interviewing a wide spectrum of physical, educational, social and emotional needs of the persons with multi disabilities was used. The sample consisted of 43 multi disable children and youth, 24 males and 19 females, from four special education centers in Bahrain managing persons with different types of disabilities- motor, blindness and intellectual. Three centers had similar pattern with the social domain on the first rank, followed by educational, physical and emotional domains. More than half of the sample, 53.5% (23 cases) was in high need to be trained for daily care and independent skills. A high percentage of the persons were in need for speech therapy, 51.3% (22 cases). The medical follow up was the highest physical need for 48.8% persons, followed by hospitalization marked by 44.2% persons. Requirment of special educational tools was the highest on the educational domain needs. The society should take care of these domains-physical, social, emotional and educational, separately and in interaction, in order to offer a fundamental environment that can allow people with multi disabilities to do the best regarding their capabilities.